Happiness, virtue and wisdom: elements of ancient Greek philosophy in Islamic advice literature - Belhaj, Abdessamad (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2024)
This essay examines the profound influence of ancient Greek philosophy on Islamic advice literature, particularly in political ethics and governance. It aims to trace the integration of Greek philosophical ideas into Islamic advice literature, focusing on four key areas: Plato's theory of happiness, Aristotle's virtue ethics, the concept of